Exploring Entrepreneurship in Academic Writing: Language Teachers’ Experiences and Emerging Opportunities at Tribhuvan University - Nepal, Shakti Raj (Educational Journal, 2025)
This article focuses on exploring entrepreneurship in language teaching and academic writing. The study primarily aims to identify potential areas for entrepreneurship in language education, with reference to academic writing. A descriptive survey design was employed for data collection, using a qualitative approach with an emphasis on observation. The study examines university teachers' involvement and engagement in relation to their professional practices. Most teachers are engaged primarily in traditional teaching-learning activities, while only a few participate in entrepreneurial endeavors. Although teachers hold academic degrees, these qualifications tend to be theoretical rather than practical or entrepreneurial in nature. There is a growing demand for entrepreneurship in language education, such as teaching, content creation, translation, transcription, academic writing, and creative arts. However, due to a lack of supportive entrepreneurial policies, many teachers are compelled to teach merely for survival. Consequently, they often express dissatisfaction with their degrees, as these have not contributed meaningfully to their livelihoods. Nonetheless, the study reveals significant potential for these skills in the global market. The implication of this article is to emphasize the need for market driven courses and academic writing opportunities in both English and Nepali language education.